ARTICULATORY AND ACOUSTIC FEATURES OF SPEECH SOUNDS AND SPEECH ORGANS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
The production and perception of speech involve a seamless interplay between articulatory mechanisms and acoustic properties. Articulatory features focus on the physical actions of speech organs such as the lungs, vocal cords, tongue, lips, and velum. These organs shape sounds based on their place of articulation (e.g., bilabial, alveolar, velar), manner of articulation (e.g., stops, fricatives, nasals), and voicing (voiced or voiceless). Vowel production, in particular, is defined by tongue position, height, and lip rounding.